(untitled) (Revista Iberoamericana de Bioética, 2018)
The consideration of the spiritual dimension of human beings is an important element in order to humanize health care. In recent decades this dimension has been incorporated into health care in such a way that, at present, the model could be considered as a “bio-pyscho-social-spiritual” model. However, said dimension tends to be dealt with from the perspective of need, a view that tend to focus on the needs of the individual. Spirituality can also be seen as a field of capabilities, of resources to better deal with the illness. This paper aims to portray that the consideration of spirituality as a source of capabilities is an important element for the humanization of health care.